A Case-Based, Longitudinal Curriculum in Pediatric Behavioral and Mental Health - Michelle E. Kiger; Lauryn Fowler; Maggie Eviston; Amanda Cook; Jason Forbush; Suzie Nelson; William Clark; Caitlin Hammond; Kara Knickerbocker; Elizabeth Gawrys-Strand; Daniel Schulteis; John Duby (MedEdPORTAL, 2024)
Introduction Pediatric behavioral and mental health (BMH) disorders are increasingly common, but most pediatricians feel inadequately trained to manage them. We implemented a case-based, longitudinal curriculum in BMH within a pediatric residency program to prepare trainees to diagnose and manage these conditions. Methods The pediatric residency program at Wright State University/Wright-Patterson Medical Center implemented a new BMH curriculum in 2020–2021. The curriculum consisted of five simulated cases involving depression, anxiety, attention deficit disorder with hyperactivity (ADHD), developmental delays, behavioral concerns, and autism. To reflect follow-up within a continuity clinic, cases included initial encounters and multiple follow-up visits. Faculty facilitators led residents in monthly small-group meetings over the academic year, with each session consisting of two to three simulated patient encounters. Residents completed pre-post surveys regarding their confidence in diagnosing and managing BMH conditions and pre- and posttests to evaluate the impact of the curriculum on knowledge gains. Results All 47 pediatric residents participated in the curriculum; 38 (81%) completed pre-post surveys. Upon completion of the curriculum, residents reported significantly increased confidence in managing ADHD, treating depression, creating safety plans for suicidality, recognizing autism, and counseling patients and families on special education services. Knowledge-based pre- and posttests completed by 25 residents (53%) also demonstrated significant improvement (M = 92.4, SD = 10.9, pre vs. M = 99.3, SD = 6.6, post, p = .009). Discussion This case-based, longitudinal curriculum in pediatric BMH simulating patient continuity improved residents’ confidence and knowledge in diagnosing and managing common BMH conditions.